Acute fatiguing effects and biomechanical characteristics of a single bout eccentric quasi-isometric resistance exercise of ankle plantar flexors - Križaj, Luka; Šarabon, Nejc; Kozinc, Žiga (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionInvestigation of the eccentric quasi-isometric (EQI) resistance exercise has started in recent years. However, the biomechanical characteristics and fatigue effects of EQI muscle actions in the ankle plantar flexors remain unexplored. This study aimed to compare the biomechanical characteristics of plantarflexion EQIs and post-EQI acute fatigue between two different loading intensities.MethodsTwenty regularly physically active participants (9 men, 11 women) completed 3 sets comprising of a single EQI muscle contraction at 75% and 90% (one intensity for each leg in a random order) of maximal voluntary isometric contraction (MVIC) on an isokinetic dynamometer. Outcome variables included total contraction time, torque impulse, angular velocities and range of motion during EQI muscle actions, as well as pre- and post-contraction MVIC measures.ResultsThe analysis indicated no statistically significant effect of EQI muscle-action on MVIC torque (main effect of time: p = 0.636). There were also no statistically significant differences between EQI muscle actions performed at 75% and 90% MVIC regarding angular velocity (p = 0.244). However, executing EQI muscle contraction at 75% MVIC resulted in statistically significantly larger total contraction time, total torque impulse, and range of motion (p < 0.001) compared to EQI at 90% MVIC.DiscussionThese findings suggest that performing EQI contractions at 75% MVIC may be more effective for generating greater mechanical stimulus without inducing significant acute fatigue.